Challenges of Teaching Legal English at a Law Higher Education Institution – Lecturers’ Voices - Nhạc, Hương Thanh; Đinh, Phương-Hoa Thị (Indonesian Journal of English Language Studies (IJELS), 2025)
English for Specific Purposes (ESP) plays a crucial role in language education, catering to the specific linguistic and communicative needs of learners in various professional and academic fields. In the context of globalization, legal English, a type of ESP language among legal professionals, has emerged as a vital component in law training programs in recent years. However, despite its growing importance, teaching legal English presents major challenges. Using a mixed-methods approach, data were collected through surveys and semi-structured interviews with legal English lecturers at a law higher education institution. The findings identify that while instructors acknowledge the importance of legal language and legal content several significant obstacles were addressed, including learners’ insufficient knowledge of English and laws, distinctive features of legal English language and law content topics, limited teaching material resources and varying student language proficiency levels.  as well as the lack of specialized training for instructors. Based on these insights, the study proposes a set of practical recommendations for professional development, material adaptation, and pedagogical strategies to maximize the quality and effectiveness of legal English education.